PENGARUH DISIPLIN DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA GURU YANG DIMODERASI OLEH BUDAYA ORGANISASIONAL SEKOLAH DASAR NEGERI UPT DISDIKPORA KECAMATAN TULIS KABUPATEN BATANG - Juremi, Juremi; Srimindarti, Ceacilia (Jurnal Ilmiah Telaah Manajemen, 2016)
This study is aimed to analyze the organizational culture role of moderating influence of discipline and organizational commitment on the performance of Public Primary School Teachers at UPT Disdikpora Tulis. In this study population is 141, where as samples taken a number of 115 respondents with a purposive sampling method. Alternative instrument used is the validity and reliability. Classical assumption used normality test, multikolonieritas test and heteroskedasticity test. While the test model used is the coefficient of determination (R²) dan F test (anova test). The hypothesis test used in this study used regression analysis with t criteria test frequency distribution for the level of significance (α) 5%. Based on research results can be summarized as follows: Discipline has positive impact on performance, Organizational commitment has positive impact on performance, Organizational culture has positive impact on performance, Organizational culture has not role of moderating influence of discipline on the performance, Organizational culture has not role of moderating influence of organizational commitment on the performance. Keywords: Discipline, Organizational Commitment, Organizational Culture and Teacher Performance